Adaptive social media management for higher education image transformation - Prabayanti, H. R.; Mustaji, Mustaji; Roesminingsih, E. (Edelweiss Applied Science and Technology, 2025)
Communication within educational institutions possesses unique characteristics, necessitating further research to identify the most suitable social media management (SMM) patterns. This study aims to develop an adaptive SMM model at Unesa, which has the potential to be replicated by other universities. The theoretical framework is based on the Circular Model of SMM (Luttrell), emphasizing the cycle of "SOME" and decentralized management principles (Blanchard), which highlight the agility of work units. Additionally, classical management theories are incorporated to support the alignment of planning and control processes. The research employs the ADDIE model, utilizing data collection techniques such as in-depth interviews, observations of faculty Instagram accounts, and surveys measuring brand image perception among 400 students. The findings reveal that the primary issue stems from the incompatibility of social media accounts across faculties with Unesa's official account, leading to fragmented institutional narratives. To address this, a solution named "Simpeten" was developed—a website-based content submission management system designed to facilitate coordination between work units and the central public relations team. The results demonstrate that the model effectively enhances the consistency of visual identity and institutional narratives. Furthermore, it is deemed suitable for replication by other campuses in Indonesia and the Southeast Asia region to bolster institutional reputation in the digital era. This research underscores the importance of integrated social media strategies and centralized content management to maintain a cohesive institutional image across multiple platforms and stakeholders.